In vitro assessment of synergistic effects in combinations of a temoporfin-based photodynamic therapy with glutathione peroxidase 1 inhibitors - Lange, Carsten; Bednarski, Patrick J. (Photodiagnosis and photodynamic therapy, 2021)
Background - Due to an increased elimination of reactive oxygen species (ROS), in particular hydrogen peroxide (H2O2), overexpression of glutathione peroxidase 1 (GPX1) can lead to an attenuation of apoptosis and development of resistance in cancer cells, thereby promoting tumor cell survival. Consequently, GPX1 inhibitors have the potential to be used in cancer therapy as they support oxidative stress in cancer cells. Similarly, photodynamic therapy (PDT) induces oxidative stress in cancer cells by the formation of ROS upon illumination. Thus, both methods of treatment might act in synergy when used in combination. - Methods - To investigate this hypothesis, combinations of the known GPX1 inhibitors 9-chloro-6-ethyl-6H-[1,2,3,4,5]pentathiepino[6,7-b]indole (CEPI) or mercaptosuccinic acid (MSA) with PDT induced by the photosensitizer (PS) temoporfin (5,10,15,20-tetra(m-hydroxyphenyl)chlorin, mTHPC) were studied in vitro. This new combinatory approach was intended to accumulate ROS formed during PDT via blockage of GPX1-catalyzed H2O2 degradation, and thus to enhance PDT-induced phototoxicity. Five human cancer cell lines from tumor origins treatable with PDT were utilized to investigate ROS generation, apoptosis induction, and cell cycle distribution. - Results - Synergy was identified with both GPX1 inhibitors, but not in all cell lines. ROS levels were increased after combined treatment with mTHPC and CEPI, but not MSA, in some cell lines, indicating that oxidative stress and ROS accumulation were enhanced by CEPI. Surprisingly, enhanced apoptosis induction was also observed with MSA afterwards, suggesting that other pathways contributed to the initiation of apoptosis. Cell cycle analysis confirmed apoptosis induction via the detection of DNA fragmentation. - Conclusion - A combination of GPX1 inhibitors with mTHPC-PDT has the potential to generate synergistic effects and to increase overall phototoxicity, but the success of this combination approach was dependent on cancer type, and even antagonistic effects can occur.
Gesehen am 10.11.2021